Powtoon Animation Video in Introduction to Literature Class: Students' Perception - Sri Yuliani; Yulianto Yulianto; Dicki Hartanto (AL-ISHLAH: Jurnal Pendidikan, 2021)
This research aimed to discover the students' perception of Powtoon animation video in Introduction to literature class. Technology had a significant impact on education. During covid-19, mostly online learning system was applied. Introduction to literature was one of the online class subjects done last semester at odd semester academic year 2020/2021 by using an online system. Sixteen meetings had been done for one semester, and the last project was creating powtoon to tell fiction stories. Thirty-five students involved in this research, and the project of powtoon was created by students as one project accomplishment in this class. The researchers set the qualitative research design by using interview. The interview result revealed that the students were enjoying creating powtoon in this class. They were motivated to use technology in the online class system and found more online media soon.